Activation-induced and damage-induced cell death in aging human T cells. (November 2015) - Sikora, Ewa
Highlights: Cell death is vital for the functionality of organism from development to aging. T cells during contraction undergo activation-induced cell death (AICD). T cells are also prone to damage-induced cell death (DICD). The changes of AICD and DICD during immunosenescence are ambiguous. Abstract: In multicellular organisms the proper system functionality is ensured by the balance between cell division, differentiation, senescence and death. This balance is changed during aging. Immunosenescence plays a crucial role in aging and leads to the shrinkage of T cell repertoire and the propensity to apoptosis. The elimination of expanded T cells at the end of immune response is crucial to maintain homeostasis and avoid any uncontrolled inflammation. Resting mature T lymphocytes, when activated via their antigen-specific receptor (TCR) and CD28 co-receptor, start to proliferate and then undergo the so called activation induced cell death (AICD), which mechanistically is triggered by the death receptor and leads to apoptosis. T lymphocytes, like other cells, are also exposed to damage, which can trigger the so called damage-induced cell death (DICD). It was hypothesized that oxidative stress and chronic antigenic load increasing with age reduced lymphocyte susceptibility to DICD and enhanced a proinflamatory status leading to increased AICD. However, data collected so far are inconsistent and does not support this assumption. Systematic and comprehensive studies are still needed for conclusive elucidation of the role of AICD and DICD in human immunosenescence, including the role of autophagy and necroptosis in the processes.